Elements of Electronic Crime - Shehab bin Abdulrahman bin Hamed Al-Masoud (International Journal of Law Research and Studies, 2025)
This study examines the crime of unauthorized access to social media platforms. The study is divided into five chapters, shedding light on the nature of this crime, the importance of criminalizing it, and delving into the elements of the crime and the corresponding penalties for perpetrators. A descriptive approach was adopted in this study to explain the concept of unauthorized access and its danger to society, while an analytical approach was used to propose systems and deterrent legislation> This thesis aims to clarify the extent of the crime’s danger and its impact on society, as well as the necessity of international cooperation to combat cybercrimes. This study has yielded several results and recommendations, most notably: if the perpetrators are from within the Kingdom, the Saudi Cybercrime Law will be applied. However, if the perpetrators are from outside the Kingdom of Saudi Arabia, I recommend the establishment of an international system issued by the United Nations for the extradition of perpetrators to be trialed, or the establishment of an international court specifically for cybercrimes. As a result, all perpetrators will face justice wherever they may be.